(untitled) (Международный научный журнал «Инженер», 2026)
The article briefly describes the historical development of aerated concrete production technology, modern methods and the contribution of Uzbek scientists to this field, and also theoretically analyzes the relationship between the thermal insulation properties of autoclaved aerated concrete and its composition, porous structure and density. The study compared aerated concrete samples with different compositions (standard, slag and sand waste variants), analyzed their thermal conductivity coefficient (λ), density (ρ) and strength. According to the results, the thermal insulation capacity of aerated concrete improved by 12–15% by adding industrial waste, and the combination of slag and sand waste gave especially optimal indicators. In addition, the fact that the λ value of aerated concrete is linearly dependent on its density was expressed through the mathematical model (λ = f(ρ)).